2018
DOI: 10.1111/lam.12852
|View full text |Cite
|
Sign up to set email alerts
|

Acetoacetate and ethyl acetoacetate as novel inhibitors of bacterial biofilm

Abstract: Bacterial biofilms are communities of bacteria that form on surfaces and are extremely difficult to remove by conventional physical or chemical techniques, antibiotics or the human immune system. Despite advanced technologies, biofilm still contributes to 60 to 80% of human bacterial infections (NIH and CDC) and cause problems in many natural, environmental, bioindustrial or food processing settings. The discovery of novel substances that inhibit biofilm without increasing the virulence of the bacteria opens d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Potentially useful microorganisms are recommended for water cooling systems [22]. To prevent the formation of biofilms, the methods of the penetration of biocides into the matrix are promising, minimizing the primary contamination and adhesion of bacterial cells is recommended, for example, the effectiveness of acetoacetate and ethyl acetoacetate as inhibitors of Y. enterocolitica biofilm has been established [23]. Monoacylglycerols with two specific segments of the fatty acid residue, monolaurin, and monoepherin have strong inhibitory activity against bacterial biofilm Y. enterocolitica that is considered a promising method for use in the food industry [24].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially useful microorganisms are recommended for water cooling systems [22]. To prevent the formation of biofilms, the methods of the penetration of biocides into the matrix are promising, minimizing the primary contamination and adhesion of bacterial cells is recommended, for example, the effectiveness of acetoacetate and ethyl acetoacetate as inhibitors of Y. enterocolitica biofilm has been established [23]. Monoacylglycerols with two specific segments of the fatty acid residue, monolaurin, and monoepherin have strong inhibitory activity against bacterial biofilm Y. enterocolitica that is considered a promising method for use in the food industry [24].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the addition of 1% tomato homogenate to the 8% EAA wash did not reduce the efficacy of the wash, which is an advantage of EAA overusing chlorine. In addition, EAA was identified as an inhibitor of biofilm on polystyrene plates by three pathogens [ 10 ] and an inhibitor of biofilm in silicone tubing by several pathogens, including S. enterica [ 11 ]. This is the second advantage of EAA over chlorine that induced the formation of biofilm [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An early study by our own research laboratory identified ß-phenylethylamine and acetoacetate as inhibitors of growth and biofilm in liquid beef broth growth medium and refrigeration temperature [ 9 ]. Ethyl acetoacetate (EAA) is chemically and structurally similar to acetoacetate but was more effective at reducing growth, live bacterial counts, and biofilm in three bacterial pathogens [ 10 ]. It is also more cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…Ham and Kim (2016) reported that monoacylglycerols with two specific lengths of fatty acid moiety, monolaurin and monobehenin at 48 mg l −1 , were found to have strong inhibitory activity towards Y. enterocolitica biofilm formation, without a clear correlation between biofilm formation and cell growth. More recently, acetoacetate and ethyl acetoacetate were found to be effective in reducing growth and biofilm amounts with IC 50 values of 14·0 and 3·2 mg l −1 for planktonic growth, respectively, and 1 mg l −1 for biofilm biomass (Horne et al 2018). In all cases, authors have not been able to find compounds that act only on biofilm formation without inhibiting cell growth.…”
Section: Discussionmentioning
confidence: 99%